2011
DOI: 10.1097/fjc.0b013e31823003f2
|View full text |Cite
|
Sign up to set email alerts
|

Different K+ Channels Are Involved in Relaxation of Arterial and Venous Graft Induced by Nicorandil

Abstract: The drug nicorandil is a vasodilator approved for the treatment of angina. In addition to its well-known effect on the opening of ATP-sensitive K (KATP) channels, nicorandil-induced vasorelaxation also involves the opening of Ca-activated K channels. The aim of this study was to investigate the effects of nicorandil on the isolated human internal mammary artery (HIMA) and the human saphenous vein (HSV) and to define the contribution of different K channel subtypes in the nicorandil action on these arterial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…ATP‐sensitive K + channels openers (K ATP COs), a class of vasodilators, such as pinacidil, nicorandil, levcromakalim and aprikalim, were found to exert their effect on vascular smooth muscles by opening ATP‐sensitive K + (K ATP ) channels, which produces hyperpolarization of the vascular cell membrane leading to vasorelaxation . K ATP channels have been first identified in cardiac muscle, and then they have been found in various cells including vascular smooth muscle .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ATP‐sensitive K + channels openers (K ATP COs), a class of vasodilators, such as pinacidil, nicorandil, levcromakalim and aprikalim, were found to exert their effect on vascular smooth muscles by opening ATP‐sensitive K + (K ATP ) channels, which produces hyperpolarization of the vascular cell membrane leading to vasorelaxation . K ATP channels have been first identified in cardiac muscle, and then they have been found in various cells including vascular smooth muscle .…”
mentioning
confidence: 99%
“…So, for example, vasorelaxation induced by K ATP CO, pinacidil, involves the opening of large-conductance K Ca (BK Ca ) channels [7,8]. Novakovic et al [2] have shown that nicorandil-induced relaxation of human saphenous vein (HSV) and human internal mammary artery (HIMA) includes activation of 4-aminopyridine (4-AP)-sensitive K + channels as well as BK Ca channels. Besides, it has been suggested that diazoxide activates K Ca channels and K V channels in smooth muscle cells by a mitochondria-dependent mechanism [9,10].…”
mentioning
confidence: 99%
“…Studies indicate that K V 1.3 have positive effects in the proliferation and cell migration, which can result in neointimal hyperplasia or vascular remodeling. Margatoxin is a potent, highly selective blocker of human K V 1.3 and has no effect on K Ca . It has been demonstrated that K V current in rat small mesenteric artery myocytes consists of two major parts, K V 1.2–1.5–β1.2 and K V 2.1–9.3, along with less functional K V 7.4 and K V 7.5, which were encoded by the KCNQ4 and KCNQ5 , and play a key functional role in regulating vascular tone .…”
Section: Basic Properties Of Potassium Channelsmentioning
confidence: 99%
“…K ATP are specifically blocked by SUR derivates such as GLI. Since GLI‐induced vasoconstriction was due to a blockade of potassium efflux from the smooth muscle cells, this suggests that under baseline conditions a potassium efflux was responsible for a certain degree of vasorelaxation . K ATP inhibitor GLI (10 μ m ) significantly inhibited both testosterone‐induced relaxation in internal spermatic vein and levosimendan‐induced relaxation in internal mammary artery .…”
Section: Basic Properties Of Potassium Channelsmentioning
confidence: 99%